Cost-effectiveness of simvastatin in people at different levels of vascular disease risk: economic analysis of a randomised trial in 20,536 individuals. - Mihaylova, B; Briggs, A; Armitage, J; Parish, S; Gray, A; Collins, R (2005)
BACKGROUND: Statin therapy reduces the rates of heart attack, stroke, and revascularisation among a wide range of individuals. Reliable assessment of its cost-effectiveness in different circumstances is needed. METHODS: 20,536 adults (aged 40-80 years) with vascular disease or diabetes were randomly allocated 40 mg simvastatin daily (10,269) or placebo (10,267) for an average of 5 years. Comparisons were made of hospitalisation and statin costs (2001 UK prices) during the scheduled treatment period between all simvastatin-allocated versus all placebo-allocated participants. Cost-effectiveness was estimated among different categories of participant. FINDINGS: Allocation to simvastatin was associated with a highly significant 22% (95% CI 16-27; p<0.0001) proportional reduction in hospitalisation costs for all vascular events, with similar proportional reductions in every subcategory of participant studied. During an average of 5 years, estimated absolute reductions in vascular event costs per person allocated 40 mg simvastatin daily ranged from UK 847 pounds sterling (SE 137) in the highest risk quintile studied to 264 pounds sterling (48) in the lowest. Mean excess cost of statin therapy among participants allocated simvastatin was 1497 pounds sterling (8), with similar absolute increases in every subcategory. Costs of preventing a major vascular event with 40 mg simvastatin daily ranged from 4500 pounds sterling (95% CI 2300-7400) among participants with a 42% 5-year major vascular event rate to 31,100 pounds sterling (22,900-42,500) among those with a 12% rate (corresponding to 5-year major coronary event rates of 22% and 4%, respectively). INTERPRETATION: Statin therapy is cost effective for a wider range of individuals with vascular disease or diabetes than previously recognised (particularly with lower-priced generics). It would be appropriate to consider reducing the estimated level of vascular event risk at which statin therapy is recommended.